Microbial Biofertilizers and Micronutrient Availability 2021
DOI: 10.1007/978-3-030-76609-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Deficiency and Its Consequences During Pregnancy

Abstract: Zinc is an important microelement that promotes immunity, proper development and growth of the nervous system and resistance to infection. It is a constituent of more than 200 enzymes involved in digestion, metabolism, synthesis of RNA and DNA, reproduction and is also essential for healthy pregnancy outcomes. An estimated 17.3% of global population is at risk for zinc deficiency due to inadequate dietary supply and bioavailability. Inadequate intake of zinc during pregnancy has been related to adverse pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Up to 90% of the total zinc in the brain comes from metalloproteins, which are proteins with zinc ions directly attached to the side chains of Cys, His, or other amino acids (Frederickson 1989 ; Anzellotti and Farrell 2008 ). DNA and RNA polymerases, respiratory enzymes, protein kinases (protein metabolism), alkaline phosphatases (blood protein breakdown), carbonate dehydratases (catalyzes carbon dioxide hydration), and lactate dehydrogenases (cell energy production) are additional non-brain zinc metalloproteins (Lewis et al 2005 ; Kibiti and Afolayan 2015 ; Durrani and Parveen 2022 ). More than 300 enzymes in animals, plants, and microbes depend on zinc for their structure, catalysis, and co-catalysis (Vallee and Falchuk 1986 ; Takeda 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Up to 90% of the total zinc in the brain comes from metalloproteins, which are proteins with zinc ions directly attached to the side chains of Cys, His, or other amino acids (Frederickson 1989 ; Anzellotti and Farrell 2008 ). DNA and RNA polymerases, respiratory enzymes, protein kinases (protein metabolism), alkaline phosphatases (blood protein breakdown), carbonate dehydratases (catalyzes carbon dioxide hydration), and lactate dehydrogenases (cell energy production) are additional non-brain zinc metalloproteins (Lewis et al 2005 ; Kibiti and Afolayan 2015 ; Durrani and Parveen 2022 ). More than 300 enzymes in animals, plants, and microbes depend on zinc for their structure, catalysis, and co-catalysis (Vallee and Falchuk 1986 ; Takeda 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other risk factors of zinc deficiency are diarrheal disease, malabsorption syndromes, parasitosis, hot and humid climate, rapid multiplicative cell growth (pregnancy, infancy, and adolescence), lactation and genetic disease. Zinc deficiency is primarily related to the poor zinc status of the diet [20]. The association between zinc deficiency and iron deficiency may be due to nutritional insufficiency of both elements or malabsorption.…”
Section: Discussion:-mentioning
confidence: 99%
“…In children, it has been associated with growth, the immune system, and cognitive performance [ 93 , 94 ]. Other risk factors of zinc deficiency are diarrheal disease, malabsorption syndromes, and parasitosis [ 95 ]. On the other hand, a study [ 96 ] conducted on Norwegian lactating mothers showed a relationship between the mother’s iodine intake and urinary iodine levels in their breastfeeding infants, confirming the link between maternal iodine intake, human milk, and therefore the iodine status of breastfeeding infants.…”
Section: Nutritional Status Of the Breastfeeding Mothermentioning
confidence: 99%